The orphan receptor GPRC5B activates pro-inflammatory signaling in the vascular wall via Fyn and NFκB - Freundt, Greta; Samson-Himmelstjerna, Friedrich Alexander von; Nitz, Jan-Thorge; Lüdde, Mark; Waltenberger, Johannes; Wieland, Thomas; Frey, Norbert; Preusch, Michael; Hippe, Hans-Jörg (Biochemical and biophysical research communications, 2022)
Background and aims: Atherosclerosis is driven by an inflammatory process of the vascular wall. The novel orphan G-protein coupled receptor 5B of family C (GPRC5B) is involved in drosophila sugar and lipid metabolism as well as mice adipose tissue inflammation. Here, we investigated the role of GPRC5B in the pro-atherogenic mechanisms of hyperglycemia and vascular inflammation. Methods: Immortalized and primary endothelial cells (ECs) and vascular smooth muscle cells (VSMCs) were used for stimulation with high glucose or different cytokines. Adenoviral-or plasmid-driven GPRC5B overexpression and siRNA-mediated knockdown were performed in these cells to analyze functional and mechanistic pathways of GPRC5B. Results: In ECs and VSMCs, stimulation with high glucose, TNFa or LPS induced a significant upregulation of endogenous GPRC5B mRNA and protein levels. GPRC5B overexpression and knockdown increased and attenuated, respectively, the expression of the pro-inflammatory cytokines TNFa, IL-1b, IL-6 as well as the pro-atherogenic vascular adhesion molecules ICAM-1 and VCAM-1. Furthermore, the expression and activity of the metalloproteinase MMP-9, a component of atherosclerotic plaque stabilization, were significantly enhanced by GPRC5B overexpression. Mechanistically, GPRC5B increased the phosphorylation of ERK1/2 and activated NFkB through a direct interaction with the tyrosine kinase Fyn. Conclusions: Our findings demonstrate that GPRC5B is upregulated in response to high glucose and pro inflammatory signaling. GPRC5B functionally modulates the inflammatory activity in cells of the vascular wall, suggesting a pro-atherogenic GPRC5B-dependent positive feedback loop via Fyn and NFkB. Thus, GPRC5B warrants further attention as a novel pharmacological target for the treatment of vascular inflammation and possibly atherogenesis. (c) 2022 Elsevier Inc. All rights reserved.